Effects of organic fertilizers on growth and biochemical characteristics of Fenugreek - Mohammad Saadatian; S. Alaghemand; H. Ayyubi; E. Hasanpour; J. A. Olfati; Y. Hamidoghli; S. Kazemi; H. Karimi (Acta Agriculturae Slovenica)
Fenugreek (Trigonella foenum-graecum L.) is an annual herb used as organic (green) manure and has medicinal applications. Organic fertilizers are used in sustainable agriculture of vegetables. Sources of organic manure and their effects on growth and yield characteristics of plants need to be determined. Effects of vermicompost and vermiwash were determined on qualitative and quantitative factors of chemical content, development and yield of fenugreek (Trigonella foenum-gaecum L.) from May to July 2012 at Agriculture College of University Guilan. A completely randomized block design with 3 replications was used. Treatments included 7 t/ha of cow manure, vermicompost, vermiwash (obtained from 7 t/ha vermicompost); 7 t/ha of leachate vermicompost + vermiwash and a control (no fertilization). Use of organic fertilizers beneficially affected plant height, pod length, pod fresh and dry mass, 1000-seed mass, plant fresh and dry mass, internode length and percents of leaves protein and nitrogen. Use of organic fertilizers may increase yield and yield components of fenugreek and its yield efficiency.